Biochemical characterization of a cyanobactin arginine-N-prenylase from the autumnalamide biosynthetic pathway. Issue 86 (4th October 2022) - Clemente, Claudia; Johnson, Nicholas; Ouyang, Xiaodan; Popin, Rafael V.; Dall'Angelo, Sergio; Wahlsten, Matti; Jokela, Jouni; Colombano, Alessandro; Nardone, Brunello; Fewer, David P.; Houssen, Wael E.
Abstract : Biochemical characterization of the prenyltransferase (AutF) from the autumnalamide pathway shows it targets the nitrogen of the guanidinium moiety in arginine and homoarginine. Abstract : Cyanobactins are linear and cyclic post-translationally modified peptides. Here we show that the prenyl-d -Arg-containing autumnalamide A is a member of the cyanobactin family. Biochemical assays demonstrate that the AutF prenyltransferase targets the guanidinium moiety in arginine and homoarginine and is a useful tool for biotechnological applications.